Extreme ultraviolet and soft X-ray imaging using compact laser-plasma sources based on a double stream gas-puff target - Wachulak, Przemysław Wojciech; Bartnik, Andrzej; Kostecki, Jerzy; Węgrzyński, Łukasz; Fok, Tomasz; Jarocki, Roman; Szczurek, Mirosław; Fiedorowicz, Henryk (Photonics Letters of Poland, 2013)
New developments in science and technology require imaging tools and techniques capable of imaging with increased contrast and high spatial resolution, such as an extreme ultraviolet (EUV) and soft X-ray (SXR) microscopy. In this paper, we report on our recent activities related to various imaging techniques in the EUV and SXR region of electromagnetic spectrum, employing a double stream gas-puff target source. Those techniques has been successfully used for studies of morphology of thin silicon membranes coated with NaCl crystals, samples composed of ZnO nanofibers and biological samples. Full Text: PDF References D. Attwood, Soft X-Rays and Extreme Ultraviolet Radiation, Cambridge University, Cambridge, England, 1999. CrossRef W. Chao, J. Kim, S. Rekawa, P. Fischer and E. H. Anderson, "Demonstration of 12 nm Resolution Fresnel Zone Plate Lens based Soft X-ray Microscopy", Opt. Express 17, 20, 17669 (2009) CrossRef G. Vaschenko, et al., "Sub- 38nm resolution tabletop microscopy with 13nm wavelength laser light", Opt.Lett. 31, 1214?1216 (2006) CrossRef C. A. Brewer, et al., "Single-shot extreme ultraviolet laser imaging of nanostructures with wavelength resolution", Opt. Lett. 33, 5, 518, (2008) CrossRef K. W. Kim, et al., "Compact soft x-ray transmission microscopy with sub-50 nm spatial resolution", Phys. Med. Biol. 51, N99-N107 (2006) CrossRef L. Juschkin, R. Freiberger, and K. Bergman, "EUV microscopy for defect inspection by dark-field mapping and zone plate zooming", J. Phys.: Conf. Ser. 186, 012030 (2009) CrossRef P. W. Wachulak, A. Bartnik and H. Fiedorowicz, "Sub-70 nm resolution tabletop microscopy at 13.8 nm using a compact laser?plasma EUV source", Opt. Lett. 35, 14, 2337-2339 (2010) CrossRef P. W. Wachulak, A. Bartnik, H. Fiedorowicz, and J. Kostecki, "A 50nm spatial resolution EUV imaging?resolution dependence on object thickness and illumination bandwidth", Opt. Exp. 19, 10, 9541?9550 (2011) CrossRef P. W. Wachulak, et al., "A compact, quasi-monochromatic laser-plasma EUV source based on a double-stream gas-puff target at 13.8 nm wavelength", Applied Physics B 100, 3, 461-469, (2010) CrossRef R. L. Kelly, Journal of Physical and Chemical Reference Data, 16, supplement 1 (1987) DirectLink The ZP was fabricated by Zone Plates Ltd., using electron beam lithography in 220nm thick PMMA (polymethyl methacrylate) layer spin- coated on top of a 50nm thick silicon nitride Si3N4 membrane. P. W. Wachulak, A. Bartnik, H. Fiedorowicz, D. Panek, P. Bruza, "Imaging of nanostructures with sub-100 nm spatial resolution using a desktop EUV microscope", Appl. Phys. B 109, 105-111 (2012) CrossRef P.W. Wachulak, et al., "Study of crystalline thin films and nanofibers by means of the laser?plasma EUV-source based microscopy", Radiation Physics and Chemistry 93, 54-58 (2013) CrossRef L.B. Da Silva, et al., "X-ray laser microscopy of rat sperm nuclei", Science 258, 269 (1992) CrossRef P. W. Wachulak, et al., "Water-window microscopy using a compact, laser-plasma SXR source based on a double-stream gas-puff target", Appl. Phys. B 111, 2, 239-247 (2013) CrossRef P. W. Wachulak, et al., "Sub 1-?m resolution ?water-window? microscopy using a compact, laser-plasma SXR source based on a double stream gas-puff target", Nucl. Instr. and Meth. B 311, 42-46(2013) CrossRef H. Wolter, "Verallgemeinerte Schwarzschildsche Spiegelsysteme streifender Reflexion als Optiken für Röntgenstrahlen", Ann. Physik 10, 286 (1952) CrossRef